Platelet Regeneration Time After Aspirin Ingestion and Platelet Survival Time After Labelling with 51Chromium or 111Indium Oxine – A Comparative Study - Boneu, A; Sié, P; Bugat, R; Caranobe, C; Eber, M; Cazenave, J P; Boneu, B (Thrombosis and Haemostasis, 1985)
A simultaneous investigation of platelet regeneration time (PRT) based upon malondialdehyde (MDA) recovery after a single oral intake of 500 mg of aspirin and of platelet survival time (PST) after labelling with 51chromium or 111Inindium oxine was performed in 25 cancerous patients. A pilot study conducted with 9 healthy volunteers demonstrated that the MDA assay was highly reproducible and specific for the platelet cycloxygenase activity. The pattern of MDA recovery after aspirin ingestion was linear in the healthy volunteers and in the patients presenting both a normal and an accelerated platelet turnover. PST were calculated using the four mathematical models recommended by the International Committee for Standardization in Hematology; the best fit was given by the multiple hit model in 22 cases and by the linear regression model in 3 cases. The mean results obtained in the patients investigated with the 51chromium were consistently shorter than those obtained in the patients investigated with the mindium oxine while the mean PRT were almost identical in the two groups. An excellent correlation between PRT and PST was observed after 111Indium oxine labelling and using the weighted mean method for PST determination. These results suggest that the 111Indium oxine technique is a better method for platelet labelling and that the results provided by the weighted mean method reflect more closely the in vivo platelet turnover than those provided by the multiple hit model.
Keywords: Platelet kinetics; Platelet survival time; Platelet regeneration time